Evaluation of mobile games in the context of content: What do children face when playing mobile games?. (September 2020) - Göksu, İdris; Aslan, Alper; Turgut, Yiğit Emrah
The aim of this study is to examine mobile games in the context of their content and to evaluate the situations faced by children through document analysis in terms of age-rating, game score, access permissions, the inclusion of advertisements, in-game purchases, encouraging consumerism, the inclusion of violence, bad habits, and educational value. The review and rating data of the games which can be found in Common Sense Media and Google Play Store were included in the study. These data were analyzed by descriptive content analysis using frequency (f) and percentage(%) values. According to our findings, it was revealed that 92% of the games involved in the study included in-game purchases and 75% of them included advertising. As a result of the investigations, it was also found that mobile games requested a lot of access permissions during installation. In addition, it was concluded that 90% of mobile games encouraged consumerism and 50% contained violence and fear elements. We think that the results are important in the way that they reveal the possible risks encountered by young people while they are playing mobile games and also in terms of increasing the awareness on the subject for both the users and their parents.